2018
DOI: 10.1039/c8qo00422f
|View full text |Cite
|
Sign up to set email alerts
|

Application of organocatalysis in bioorganometallic chemistry: asymmetric synthesis of multifunctionalized spirocyclic pyrazolone–ferrocene hybrids as novel RalA inhibitors

Abstract: Asymmetric construction of chiral spirocyclic pyrazolone–ferrocene hybrids has been developed. The lead compound displayed potent RalA inhibition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 49 publications
(31 citation statements)
references
References 49 publications
0
31
0
Order By: Relevance
“…Derivative 72 (Fig. 6), as the most promising anticancer candidate, was designed and synthesized by Zhang and colleagues [56]. The consequence for ability of compound 72 inducing apoptotic death in PANC-1 cells showed that derivative 72 suppressed RalA according to inducing the accumulation of ROS and trigger mitochondrial apoptosis in PANC-1 cells.…”
Section: C-met Target Inhibitorsmentioning
confidence: 99%
“…Derivative 72 (Fig. 6), as the most promising anticancer candidate, was designed and synthesized by Zhang and colleagues [56]. The consequence for ability of compound 72 inducing apoptotic death in PANC-1 cells showed that derivative 72 suppressed RalA according to inducing the accumulation of ROS and trigger mitochondrial apoptosis in PANC-1 cells.…”
Section: C-met Target Inhibitorsmentioning
confidence: 99%
“…For western blotting, the total protein extracts from each sample were processed as previously described [72][73][74][75]. The total proteins were loaded into the SDS-PAGE (sodium dodecyl sulfate-polyacrylamide) gel and separated by their molecular weight via electrophoresis (PAGE).…”
Section: Western Blotting Analysismentioning
confidence: 99%
“…In order to assess the possibility of subroutine cell death underlying 8m treatment, flow cytometry with annexinV/PI dual staining was used to assess the activation of apoptosis [39][40][41][42][43][44][45] . Hoechst 33258 staining also clearly showed that nuclear morphological changes in apoptotic cells, including chromatin condensation and apoptotic bodies, mediated apoptosis ( Figure 5(D)).…”
Section: Novel Hsp90/pi3ka Dual Inhibitors 8m Suppressed Cell B16 Melmentioning
confidence: 99%